The many facets of MLL1 regulation1. Issue 2 (22nd November 2012) - Zhang, Pamela; Bergamin, Elisa; Couture, Jean‐François; Trievel, Ray
Abstract In the last 20 years, we have witnessed an exponential number of evidences linking the human mixed lineage leukemia‐1 (MLL1) gene to several acute and myelogenous leukemias. MLL1 is one of the founding members of the SET1 family of lysine methyltransferases and is key for the proper control of developmentally regulated gene expression. MLL1 is a structurally complex protein composed of several functional domains. These domains play pivotal roles for the recruitment of regulatory proteins. These MLL1 regulatory proteins (MRPs) dynamically interact with MLL1 and consequently control gene expression. In this review, we summarize recent structural and functional studies of MRPs and discuss emergent structural paradigms for the control of MLL1 activity. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 136–145, 2013.